2019
DOI: 10.12991/jrp.2019.145
|View full text |Cite
|
Sign up to set email alerts
|

The effects of riboflavin on ischemia/reperfusion induced renal injury: Role on caspase-3 expression

Abstract: Reactive oxygen metabolites play important roles in ischemia/reperfusion (I/R) injury in several organ systems. Riboflavin has been shown to exert antioxidant and/or anti-inflammatory activities in several experimental models. The aim of this study was to investigate the role of riboflavin against I/R injury in the rat kidney. Wistar albino rats 200-300 g weighing were divided into 3 groups. One week after unilateral nephrectomy, the IR procedure was applied to the rats. To induce I/R injury renal pedicle was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, beneficial effects of riboflavin on renal function biomarkers in renal toxicity (23) , biomarkers of liver function, inflammation and lipid profile in hepatotoxicity (26) , biomarkers of renal and liver function and fasting blood glucose in diabetes (31) , and markers of pulmonary permeability in lung injury (22) have been reported. Furthermore, as discussed in our previous review (12), riboflavin has also shown to have a protective effect against reperfusion oxidative injury (the tissue damage occurs after a period of ischemia as a result of blood reperfusion) of different organs in experimental models, a finding which has been supported by the recent findings (59)(60)(61)(62) . Therefore, the antioxidant effects of riboflavin could make it a potential therapeutic agent in mentioned conditions and other diseases in which oxidative stress is involved.…”
Section: Clinical Outcomesmentioning
confidence: 65%
“…Moreover, beneficial effects of riboflavin on renal function biomarkers in renal toxicity (23) , biomarkers of liver function, inflammation and lipid profile in hepatotoxicity (26) , biomarkers of renal and liver function and fasting blood glucose in diabetes (31) , and markers of pulmonary permeability in lung injury (22) have been reported. Furthermore, as discussed in our previous review (12), riboflavin has also shown to have a protective effect against reperfusion oxidative injury (the tissue damage occurs after a period of ischemia as a result of blood reperfusion) of different organs in experimental models, a finding which has been supported by the recent findings (59)(60)(61)(62) . Therefore, the antioxidant effects of riboflavin could make it a potential therapeutic agent in mentioned conditions and other diseases in which oxidative stress is involved.…”
Section: Clinical Outcomesmentioning
confidence: 65%